Pendampingan Edukasi Pembukuan Transaksi Keuangan Sederhana pada Kelompok Tani Jaya Bersama Desa Tanjung Dalam Curup Selatan - Syafitri, Twenty Mariza; Wulandari, Sri; Effendi, Darwan; Anbare, Intan; Fransisco, Rhamos (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Farmer groups are one of the economic drivers in rural areas which are managed by local village communities. Tanjung Dalam Village has the main commodity, namely coffee. The aim of this Community Service is to help with the problems being faced by farmer groups in Tanjung Dalam Village. The main problem faced by service partners is a lack of knowledge regarding financial management in small businesses. This is evidenced by the lack of financial administration activities carried out by the Tani Jaya Bersama Group, such as archiving transaction evidence, recording transactions and financial bookkeeping. The method applied in this activity is through an educational approach. The result of this service activity is that service partners have been able to understand the basics of recording financial transactions and carrying out simple financial bookkeeping. which can support the progress of their business in the future. The evaluation results of service activities found that 80% of participants had understood and implemented simple financial recording and bookkeeping.